Influence of Prescribed Herbal and Western Medicine on Patients with Abnormal Liver Function Tests: A Retrospective Quasi-Experimental Study - Lee Ah-Ram; Yim Je-Min; Kim Won-Il (Korean Pharmacopuncture Institute, 2012)
Objectives: The aim of this study was to investigate the safety and the efficacy of Korean herbal, western and combination medicine use in patients with abnormal liver function tests. Methods: We investigated nerve disease patients with abnor-mal liver function tests who were treated with Korean herbal, western and combination medicine at Dong-Eui University Oriental Hospital from January 2011 to August 2011. We co-mpared aspartic aminotransferase (AST), alanine aminotran-sferase (ALT), alkaline phosphatase (ALP) and total bilirubin (T-bil) levels before and after taking medicine and excluded patients who had liver-related disease when admitted. Results: AST and ALT were decreased significantly in patients who had taken herbal, western medicine. AST, ALT and ALP were decreased significantly in patients who had taken comb-ination medicine. Compare to herbal medicine, AST, ALT and ALP were decreased significantly in patients who had taken western medicine, and ALT and ALP were decreased signifi-cantly in patients who had taken combination medicine. There were no significant differences between western and combin-ation medicine. Conclusions: This study suggests that prescribed Korean herbal medicine, at least, does not injure liver function for patients', moreover, it was shown to be effective in patients with abnormal liver function tests.